2011
DOI: 10.1371/journal.pone.0027974
|View full text |Cite
|
Sign up to set email alerts
|

The Communicability of Graphical Alternatives to Tabular Displays of Statistical Simulation Studies

Abstract: Simulation studies are often used to assess the frequency properties and optimality of statistical methods. They are typically reported in tables, which may contain hundreds of figures to be contrasted over multiple dimensions. To assess the degree to which these tables are fit for purpose, we performed a randomised cross-over experiment in which statisticians were asked to extract information from (i) such a table sourced from the literature and (ii) a graphical adaptation designed by the authors, and were ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Gelman and others (Cleveland, 1984;Gelman et al, 2002;Kastellec and Leoni, 2007) have identified a need for greater use of graphs in statistics and allied disciplines literature. Cook and Teo (2011) recommended the use of graphs over tables based on the speed and accuracy with which information about statistical simulation studies could be decoded. However, the skeptics or "table people" (Friendly and Kwan, 2011) are unlikely to be convinced of the power of graphics without examples of graphical excellence.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Gelman and others (Cleveland, 1984;Gelman et al, 2002;Kastellec and Leoni, 2007) have identified a need for greater use of graphs in statistics and allied disciplines literature. Cook and Teo (2011) recommended the use of graphs over tables based on the speed and accuracy with which information about statistical simulation studies could be decoded. However, the skeptics or "table people" (Friendly and Kwan, 2011) are unlikely to be convinced of the power of graphics without examples of graphical excellence.…”
Section: Accepted Manuscriptmentioning
confidence: 99%